The influence of anxiety on sociocultural adjustment among international students in Malaysia - Abdul Talib, Asmat Nizam; Abdul Malek, Marlin Marissa; Jaguli, Abd Rahim; Husin, Hartini (2015)
The main purpose of this study is to investigate whether anxiety will inversely influence international students’ socio cultural adjustment in the context of pursuing education in higher learning institutions in Malaysia; specifically in Universiti Utara Malaysia.The data used for this study was derived from the questionnaire survey conducted randomly among the international students in Universiti Utara Malaysia (UUM) who came from 27 different nationalities.A total number of 397 valid responses were successfully obtained.Multiple regression analysis was performed to test the model.For the relationship between anxiety and socio cultural adjustment, although a significant relationship is found, the direction of the postulated relationship is positive instead of negative.The result may have some implications to management and policy makers.